2000
DOI: 10.1093/bja/85.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on hypoxic pulmonary vasoconstriction in anaesthetized piglets

Abstract: In vitro, halogenated agents reduce the pulmonary vasoconstrictor response to alveolar hypoxia in isolated perfused lungs. However, studies in intact animals have been less convincing. The aim of the present study was to assess the effect of sevoflurane on hypoxic pulmonary vasoconstriction (HPV) in anaesthetized piglets using the pressure/cardiac index relationship (P/Q). Ten large white piglets were anaesthetized and mechanically ventilated, alternately in hyperoxia (FIO2 = 0.4) and hypoxia (FIO2 = 0.12). Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…This technique has already been used in mammals to test the effects of anesthetics 5 and of physiologic or metabolic manipulations on HPV. 16,17 The P/Q plots in our piglets were linear in all experimental conditions, in keeping with previous studies in intact anaesthetized 5,6 or unsedated animals. 12 HPV shows a large inter-individual and inter-species variability.…”
Section: Desflurane In Hypoxiasupporting
confidence: 89%
See 3 more Smart Citations
“…This technique has already been used in mammals to test the effects of anesthetics 5 and of physiologic or metabolic manipulations on HPV. 16,17 The P/Q plots in our piglets were linear in all experimental conditions, in keeping with previous studies in intact anaesthetized 5,6 or unsedated animals. 12 HPV shows a large inter-individual and inter-species variability.…”
Section: Desflurane In Hypoxiasupporting
confidence: 89%
“…11 Pulmonary hemodynamics were evaluated by multipoint pulmonary vascular pressures -flow plots (P/Q plots) which provide a quantitative characterization of the pulmonary vascular pressure (P)-cardiac output (Q) relationship. 6,7 Previous experiments have demonstrated that these plots are linear in intact anesthetized piglets. 12 M Ma at te er ri ia al l a an nd d m me et th ho od ds s All experimental procedures were reviewed and approved by the Animal Ethics Committee of La Timone Medical School in Marseille.…”
Section: [La Vasoconstriction Pulmonaire Hypoxique N'est Pas Inhibée mentioning
confidence: 94%
See 2 more Smart Citations
“…However, it has a number of limitations including systemic hypotension, changes in blood gases and changes in zonal conditions of the lung. This technique has already been used in mammals to test anaesthetic effects [12,13] and physiological or metabolic manipulations on HPV [7,14].…”
Section: Discussionmentioning
confidence: 99%